General Assembly of Twisted Trigonal‐Prismatic Nonanuclear Silver(I) Clusters. Issue 9 (25th January 2016) - Li, Xiao‐Yu; Su, Hai‐Feng; Zhou, Rui‐Qi; Feng, Sheng; Tan, Yuan‐Zhi; Wang, Xing‐Po; Jia, Jiong; Kurmoo, Mohamedally; Sun, Di; Zheng, Lan‐Sun
Abstract: A general class of C 3 ‐symmetric Ag9 clusters, [Ag9 S( t BuC6 H4 S)6 (dpph)3 (CF3 SO3 )] (1 ), [Ag9 ( t BuC6 H4 S)6 (dpph)3 (CF3 SO3 )2 ]⋅ CF3 SO3 (2 ), [Ag9 ( t BuC6 H4 S)6 (dpph)3 (NO3 )2 ]⋅ NO3 (3 ), and [Ag9 ( t BuC6 H4 S)7 (dpph)3 (Mo2 O7 )0.5 ]2 ⋅ 2 CF3 COO (4 ) (dpph=1, 6‐bis(diphenylphosphino)hexane), with a twisted trigonal‐prism geometry was isolated by the reaction of polymeric {(HNEt3 )2 [Ag10 ( t BuC6 H4 S)12 ]} n, 1, 6‐bis(diphenylphosphino)hexane, and various silver salts under solvothermal conditions. The structures consist of discrete clusters constructed from a girdling Ag9 twisted trigonal prism with the top and bottom trigonal faces capped by diverse anions (i.e., S 2− and CF3 SO3 − for compound1, 2×CF3 SO3 − for compound2, 2×NO3 − for compound3, and t BuC6 H4 S − and Mo2 O7 2− for compound4 ). This trigonal prism is bisected by another shrunken Ag3 trigon at its waist position. Interestingly, two inversion‐related Ag9 trigonal‐prismatic clusters are dimerized by the Mo2 O7 2− ion in compound4 . The twist is amplified by the bulkier thiolate, which also introduces high steric‐hindrance for the capping ligand, that is, the longer dpph ligand. Four more silver–sulfur clusters (namely, compounds5 –8 ) with their nuclearity ranging from 6–10 were solely characterized by single‐crystal X‐ray diffraction to verify the above‐described synergetic effect of mixed ligands in the construction of Ag9 twisted trigonal prisms. Surprisingly, only cluster1 emits yellow luminescence at λ =584 nm at room temperature, which may be attributed to a charge transfer from the S 3p orbital to the Ag 5s orbital, or mixed with metal‐centered (MC) d 10 →d 9 s 1 transitions. Upon cooling from 300 to 80 K, the emission intensity was enhanced along with a hypsochromic shift. The good linear relationship between the maximum emission intensity and the temperature for compound1 in the range of 180–300 K indicates that this is a promising molecular luminescent thermometer. Furthermore, cyclic voltammetric studies indicated that the diffusion‐ and surface‐controlled redox processes were determined for compounds1 and3 as well as compound4, respectively. Abstract : Beautiful mind : A general class of C 3 ‐symmetric Ag9 clusters with twisted trigonal‐prismatic geometry was synthesized and characterized (see figure). The twisted geometry appears to be exerted by the bulky thiolate, which also introduces a high steric‐hindrance requirement for the capping ligand, that is, the longer 1, 6‐bis(diphenylphosphino)hexane ligand.